Development of English Learning Models for Special Purposes - Sri Rahayu (Budapest International Research and Critics University, 2022)
English is one of the most studied and used international languages in communicating between nations. English acts as a global or world language because English is studied and used as a means of communication in various countries, both as a first language, second language, and as a foreign language, English as a foreign language is the first to be studied as a subject taught from the level of early childhood education. /kindergarten to college. Not only that, there are many facts that show that English is able to provide significant added value for the workforce who master it, facilitate activities in the international world, and provide its own competitiveness in obtaining better job opportunities. This study uses a descriptive type of research with a qualitative approach, the researcher also wants to discuss the phenomenon entitled the development of an English learning model for special purposes, while what is meant by the qualitative method is an inductive research, the researcher allows problems to arise from the data or in leave it open for interpretation, while the results of this study explain that, English has a very important role in the current era of globalization, besides that English is also very necessary both in mastering communication technology and in interacting directly. As a means of global communication, English has a very strategic role in achieving the success of one's career, one of which can be done with the English For Specific Purposes (ESP) approach. English for Specific Purposes (ESP) or English for special purposes is a new approach in teaching and using English for special fields and studies that are in accordance with the needs of the fields of knowledge and professions that use English. ESP programs and materials are goal oriented which are targeted to be achieved at each meeting. This goal is understood as the benefits of English in playing its role as a communication tool to convey ideas related to certain contexts. ESP programs and materials should be designed and developed so that ESP plays a role in improving the English language competence of students or groups of individuals studying English specifically.